Analysis of Electromagnetic Interference and Shielding in the μLED Optrode Based on Finite Element Method - Wang, Yang; Li, Yamin; Yang, Xiaowei; Wu, Xiaoting; Wang, Yijun; Pei, Weihua (Frontiers in Nanotechnology, 2021)
Monolithic integrated μLED optrode has promising applications in optogenetics due to their ability to achieve more optical channels in a smaller footprint. The current used to drive the μLED will cause electromagnetic interference (EMI) noise to the recording electrodes at a very close distance. Utilizing a grounded metal shielding layer between the active device and the electrode can potentially reduce the interference. In this paper, multi-dimensional μLED optrode models are set up according to the real device. By numerically analyzing the electromagnetic interference between the μLED and recording electrodes, several optimized shielding schemes are evaluated by simulations and experiments. Some important process and layout parameters that may influence the shielding effect are studied through the finite element method (FEM). Different circuit models based on the corresponding test environment are built to analyze the simulation and experiment results. A new PCB with a shielding layer has been designed and initially verified. And a novel simulation model is proposed to analyze electromagnetic interference quantitatively. With these methods, low-noise μLED optrode can be fabricated by reasonably designed shielding layers and package.